Immune reconstitution disease or mycobacteria other than tuberculosis or both: A dilemma in a patient of AIDS - Shah, Arti (Medknow Publications & Media Pvt Ltd, 2012)
A 35-year-old male diagnosed as HIV with tuberculous lymphadenopathy, presented with acute increase in size of neck swelling and fever. The patient was on antiretroviral therapy and antitubercular treatment. Investigations revealed raised CD4 counts and the pus from swelling showed mycobacteria other than tuberculosis (MOTT) on bacteriological examination.The patient was started on steroids, azithromycin, and ciprofloxacin to which he responded well. We report this case to highlight the occurrence of immune reconstitution disease in HIV patients and also to bring out the fact that atypical infection like MOTT may confound the diagnosis even in regions like ours where MOTT is rarely reported.